Arachidonic acid and eicosapentaenoic acid metabolism in juvenile Atlantic Salmon as affected by water temperature - F Norambuena; S Morais; JA Emery; GM Turchini (2015)
Salmons raised in aquaculture farms around the world are increasingly subjected to sub-optimal environmental conditions, such as high water temperatures during summer seasons. Aerobic scope increases and lipid metabolism changes are known plasticity responses of fish for a better acclimation to high water temperature. The present study aimed at investigating the effect of high water temperature on the regulation of fatty acid metabolism in juvenile Atlantic salmon fed different dietary ARA/EPA ratios (arachidonic acid, 20:4n-6/ eicosapentaenoic acid, 20:5n-3), with particular focus on apparent in vivo enzyme activities and gene expression of lipid metabolism pathways. Three experimental diets were formulated to be identical, except for the ratio EPA/ARA, and fed to triplicate groups of Atlantic salmon (Salmo salar) kept either at 10°C or 20°C. Results showed that fatty acid metabolic utilisation, and likely also their dietary requirements for optimal performance, can be affected by changes in their relative levels and by environmental temperature in Atlantic salmon. Thus, the increase in temperature, independently from dietary treatment, had a significant effect on the β-oxidation of a fatty acid including EPA, as observed by the apparent in vivo enzyme activity and mRNA expression of pparα -transcription factor in lipid metabolism, including β-oxidation genes- and cpt1 -key enzyme responsible for the movement of LC-PUFA from the cytosol into the mitochondria for β-oxidation-, were both increased at the higher water temperature. An interesting interaction was observed in the transcription and in vivo enzyme activity of Δ5fad-time-limiting enzyme in the biosynthesis pathway of EPA and ARA. Such, at lower temperature, the highest mRNA expression and enzyme activity was recorded in fish with limited supply of dietary EPA, whereas at higher temperature these were recorded in fish with limited ARA supply. In consideration that fish at higher water temperature recorded a significantly increased feed intake, these ...